Effects of surface treatments on the bond strength between resin cement and a new zirconiareinforced lithium silicate ceramic - Sato, T. P. [UNESP]; Anami, L. C. [UNESP]; Melo, R. M. [UNESP]; Valandro, L. F.; Bottino, M. A. [UNESP] (My University, 2016)
This study evaluated the effects of surface treatments on the bond strength between the new zirconia-reinforced lithiumsilicate ceramic (ZLS) and resin cement. VITA Suprinity blocks were crystallized according to the manufacturer's instructions and randomly assigned to six groups (N=36; n=6), according to the surface treatment to be performed and aging conditions: HF20, 10% hydrofluoric acid for 20 seconds, baseline (control);HF20tc, 10%hydrofluoric acid for 20 seconds, aging; HF40, 10% hydrofluoric acid for 40 seconds, baseline; HF40tc, 10% hydrofluoric acid for 40 seconds, aging; CJ, CoJet sandblasting (25 seconds, 2.5 bar, 15-mm distance), baseline; and CJtc, CoJet sandblasting (25 seconds, 2.5 bar, 15-mm distance), aging. All specimens were silanized (Monobond S) and cemented with Panavia F to newly polymerized Z250 resin blocks. After specimens were immersed for 24 hours in distilled water at 378 C, 1-mm2 cross-sectionmicrobars were obtained by means of a cutting machine under constant cooling. Baseline groups were immediately tested, whereas tc groupswere used to analyze the effect of aging on bond strength (10,000 thermal cycles, 5/558C, 30-second bath). The microtensile bond strength test was performed with a universal testing machine (0.5 mm/min), and bond strength (MPa) was calculated when the load-tofailure (N) was divided by the adhesive area (mm2). We also evaluated the surface roughness (Sa, average roughness; Str, texture aspect ratio; Sdr, developed interfacial area ratio) and the contact angle resulting from the treatments. Data were statistically analyzed by one-or twoway analysis of variance and Tukey's test (all a=5%). The failure mode of each specimen was evaluated by stereomicroscopy, and representative specimens were analyzed by scanning electron microscopy. The microtensile bond strength was affected by the surface conditioning (p,0.0001), storage condition (p,0.0001), and the interaction between them (p=0.0012). The adhesion for HF etching was stable, whereas for CJ, aging significantly damaged the adhesion. Most failures were predominantly adhesive between ceramic and cement (52.6%). The roughness of the treated samples was higher compared with that of polished specimens for the three evaluated parameters (Sa, Str, and Sdr; all p,0.0001). Contact angle was also influenced by treatments (p,0.0001), with the CJ group showing values similar to those of control specimens. It can be concluded that the three surface treatment techniques present favorable immediate results, but silica coating was not effective in maintaining the bond strength over the long term.